2011
DOI: 10.12968/jowc.2011.20.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Survey of fungi and yeast in polymicrobial infections in chronic wounds

Abstract: This microbial survey shows that fungi are more important wound pathogens and opportunistic pathogens than previously reported, exemplifying the impact of these under-reported pathogens. With the application of modern cost-effective and comprehensive molecular diagnostics, clinicians can now identify and address this significant component of chronic wound bioburden with targeted therapies, thereby improving healing trajectories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(106 citation statements)
references
References 72 publications
2
101
0
1
Order By: Relevance
“…Chronic infections such as chronic wounds comprise 60-80% of infectious diseases in humans [20]. Colonisation of fungi in wounds is associated with the use of broadspectrum antibiotics [21].…”
Section: Fusarium Biofilmsmentioning
confidence: 99%
“…Chronic infections such as chronic wounds comprise 60-80% of infectious diseases in humans [20]. Colonisation of fungi in wounds is associated with the use of broadspectrum antibiotics [21].…”
Section: Fusarium Biofilmsmentioning
confidence: 99%
“…These results are in agreement with the findings of Dowd SE et al 13 Samples from unopened abscess cavities and surgical sites showed no growth of fungi. 14 From skin and its appendages dermatophytes were the major isolates consisting of Trichophyton rubrum, T. mentagrophyte, Microsporum and Epidermophyton spp. followed by the Candida.…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 7-23% of chronic wounds contain fungi. 32,33 The figure rises slightly to 27% in infected diabetic wounds requiring hospitalisation for treatment. 34 A study from 2012 has demonstrated that such patients show marked improvement in wound healing rates when treated with an antifungal compared with a best standard care control.…”
Section: Resultsmentioning
confidence: 99%